The Territory Paradox: the Basis of Statehood and International Norms as an Obstacle to the Protection of International Community Interests - Carrillo-Santarelli, Nicolás (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The role of effectiveness as a criterion to determine the success of territorial unity or secession not only fails to settle tensions between some principles of international law, such as those of territorial integrity and self-determination, but also creates certain legal paradoxes. Those paradoxes are generated partly because some norms and interpretations remain excessively attached to territorial criteria, leading to a dissociation with a globalized world in which transnational actors operate and borders are practically eroded or ignored. A humanized approach that responds to both State and non-state challenges must be adopted to deal with those tensions and paradoxes, granting remedial independence in extreme cases in which it is the only way to protect from serious breaches of peremptory law, even when secession is not successfully achieved, thus justifying it; forbidding the legal effects of effective situations achieved in ways contrary to jus cogens; and permitting or even demanding protection from non-state abuses originating in foreign territories, such as those attributable to armed groups or transnational businesses.
Keywords: integralność terytorialna; prawa człowieka; skuteczność; państwowość; podmiot niepaństwowy (NSA); jus cogens